АНАЛИЗ НЕКОТОРЫХ АФФИКСАЛЬНЫХ ПРОИЗВОДНЫХ СУЩЕСТВИТЕЛЬНЫХ - Жалгасов, Н.; Тлектесов, Ф. (SCIENCE and SOCIETY, 2017)
The article deals with derivative nouns formed by means of affixation, particularly, suffixation which is considered to be the most productive way in the formation of derivative nouns. In the article it’s given a large group of suffixes that take part in the formation of nouns from different stems which are verbs, nouns, adjectives etc. Besides the author pays a great attention to the semantic peculiarities of newly-formed derivative nouns. The analysis of examples coincides with the points of view of the author.